The Effect of Profitability, Company Size, Capital Structure on Companies Value and Corporate Governance as Moderation Variables - Septiana, Eva Dwi; Nurcahyono, Nurcahyono (Economics and Business International Conference Proceeding, 2024)
The purpose of this study is to examine the influence of Profitability, Company Size, Capital Structure on the value of Good Corporate Governance companies as moderation variables in the energy sector listed on the Indonesia Stock Exchange in 2020-2023. The sample of this study was selected using the purposive sampling method. This study looked at 14 companies in the energy sector. The content analysis method is used to collect information about the company's value in the company's annual financial report. This study shows that Profitability has no effect on company value, Company Size has no effect on company value, Capital Structure has no effect on company value, and Managerial Ownership has no effect on company value.